Impact of crushed sand on the properties of black cotton soil. - G. Rathod, Rajshekhar; Kishor Ravande, Dr; K. Laigude, Gaurav; D. Dama, Utkarsh; S. Bhoite, Priyanka (International Journal of Engineering and Technology, 2018)
Black cotton soil is generally found in western and southern parts of India. Nowadays inefficient properties of soil are critical issues in highway projects. In that case, improve the characteristics of unsuitable soil is fundamental step for the construction. Pavement structure on poor soil subgrades shows distress causing the failure of pavements. Clayey soil usually have the potential to demonstrate and desirable engineering behavior such as load bearing capacity, high shrinkage, swelling characteristics and high moisture susceptibility.Stabilization of Clayey soil is usual practice for improving strength. Soil Stabilization performed the use of technique to adding a binder to the soil in order to improve the engineering properties of soil. This research work reports the improvement in the locally available clayey soil by addition of crushed sand. In this paper the experimental results obtained in the laboratory on black cotton soil treated with lost cost material such as crushed sand. A study is carried out to check the improvement in the properties of black cotton soil with crushed sand in varying percentage. The test results such as Sieve Analysis, Atterbergs limits, Specific gravity, Compaction test and Unconfined compression test at different proportions of crushed sand. The result shows that stabilized black cotton soil has improved the bearing capacity, lesser swelling and reduction in shrinkage has been observed.Â